What attracts executives to move from large to medium-sized enterprises? - Borg Cardona, Etienne (Cranfield University, 2023)
Various studies have highlighted the importance of talented human capital to organisations in their quest for commercial success and competitive advantage. Studies in diverse fields including HRM, organisational attractiveness and, more recently, employer branding, have sought to address the important question: how can organisations attract high calibre management? At the same time, mounting evidence indicates that SMEs experience unique difficulties in attracting senior executive talent, and that this problem is the major limiting factor to their growth, development, and ultimately, survival. A systematic review of the literature revealed that no research exists on what attracts executives to SMEs, therefore it was necessary to return to the wider attraction literature to synthesise existing theoretical frameworks into an integrated model. This provided a basis for a qualitative study using interviews with executives who had left large organisations to join medium-sized enterprises. This study makes three contributions to theory. Firstly, it proposes a model that describes attraction of executives to medium-sized enterprises. The model integrates both organisational-related and employer-related attraction factors, sheds light on which job and organisational attributes are seen as important attraction factors by executives, and introduces novel attributes that positively impact attraction in the research context. Secondly, in explaining what attracts executives to medium-sized enterprises, this study lends support to the emerging compensatory theory of employer attractiveness. Thirdly, this research reveals the existence of three distinct profiles of executive job seekers who take up jobs in medium- sized enterprises.
Keywords: Organisational attractiveness; organisational reputation; organisational image; employer branding; medium-sized enterprises; SMEs; executives